Mouth and Gut Development of Malaysian River Catfish Mystus Nemurus (Cuvier and Valenciennes) Larvae - Elhag, Ghada Ahmed (2000)
Ontogenetic changes in mouth and gut during larval developmental stage of Malaysian river catfish, Mystus nemurus were studied for 21 days to facilitate and determine the suitable feed and feed particle size for the growing larvae. The eggs began to hatch at day 2 after fertilization (DAF) and most of the larvae hatched within 2-4 DAF. The larval mouth was opened at the end of the first day after hatching (DAR) and the commencement of exogenous feeding was began on the 4 DAH after the movement of jaws. The barbels began to appear on the upper jaw and lower jaw on 3 DAR, and two small barbels appeared around olfactory pits by 5 DAR. Free neuromasts were observed under the lower jaw on 7 DAR and around the olfactory pits, the eyes, and upper operculum by the 9 DAH. Strong (Ma = 5.5108 TL + 47.16, R2 = 0.9302 at 45° opening and Ma = 10.138 TL + 87.141, R2 = 0.9302 at 90° opening) relationships were found to exist between mouth size and total length of fish. The morphological and histological development of the gut in M nemurus larvae was observed using a profile projector and a light microscope. During the yolk absorption period, the gut was a simple, straight, undifferentiated tube throughout its length. By 4-5 DAR, the gut differentiated to the oesophagus, stomach, and intestine. At the first feeding, the larval gut was functional, but was structurally and functionally less complex than that of adults. By the 13 DAH, four developed tissue layers (mucosa, submucosa, muscularis and serosa) were observed in the larval gut which are the characteristics of the gut of an adult vertebrate.